A catalog and distributional analysis of the Rutelinae (Coleoptera: Scarabaeidae) of Ecuador - Paucar-Cabrera, Aura (Zootaxa, 2005)
Research on the Ecuadorian Rutelinae (Coleoptera: Scarabaeidae) was conducted to determine the diversity of the group in Ecuador and to examine distributional patterns. Results showed that the Rutelinae are distributed in all zoogeographical zones of the country except the Galápagos Islands. Species of Rutelinae occupy a wide variety of habitats ranging from sea level to the high Andes. Areas with the greatest diversity of species, in decreasing order, are the tropical habitats on both sides of the Andes, the subtropical, and the temperate zones. Ecuador has 298 species and 53 genera of Rutelinae. In sum, 36% of the species are endemic to Ecuador.Se realizó un estudio faunístico con el objetivo de conocer la biodiversidad de Rutelinae (Coleoptera: Scarabaeidae) en el Ecuador. Los resultados muestran que la subfamilia Rutelinae está distribuida en todos los pisos zoogeográficos del Ecuador excepto en Galápagos. Las especies de Rutelinae ocupan una amplia variedad de hábitats desde el nivel del mar hasta el piso alto andino. Las áreas con mayor diversidad de especies, en orden decreciente, son los pisos tropicales, subtropicales y temperado. Ecuador tiene 298 especies y 53 géneros de Rutelinae. El 36% de las especies son endémicas.